Academic distress, perceived stress and coping strategies among dental students in Saudi Arabia - Zeyad H. Al-Sowygh (Saudi Dental Journal)
Objectives: To evaluate the sources of stress among students in the dental school environment, their perceived levels of stress and effective coping strategies. Methods: This study was conducted during the first semester of the academic year, 2009–10, at the College of Dentistry, King Saud University, Saudi Arabia. The eligible study group consisted of 556 undergraduate dental students from all five class years; they were surveyed with a detailed assessment tool. The validated and translated questionnaire comprised the modified version of the dental environmental stress (DES) survey, the perceived stress scale (PSS) and the brief coping scale (BCS). Results: The overall findings substantiated with multiple regression indicate that, out of 20 factors of both DES and BC instruments, six factors were significantly and independently related to perceived stress scores (F = 34.638; p < 0.0001). Especially, the factors self-efficacy and workload of DES and the factors behavioral disengagement, denial, positive reframing and venting of BC were positively and independently related to perceived stress scores. Conclusions: Dental students displayed relatively high perceived stress scores. Female, advanced and married, compared with male, junior and single students reported more stress. Changes in certain environmental factors and coping strategies independently affected the perceived stress score. Strategies for stress management must be incorporated into dental education to ensure the output of effective dentists. Keywords: Dental environmental stress, Perceived stress scale, Brief coping scale, Stress study, Dental students